ESTABLISHING "GOOD MORNING PROGRAM" TO PROMOTE ENGLISH FOR YOUNG LEARNERS - Bambang Harmanto (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
The teaching English to young children has become important in Indonesia in recent years. It means that the role and importance of English has got serious attention. Parents and educational leaders see early English education as a necessary prerequisite for children's later success. The underlying assumption is that learners will be more successful if they begin studying English at early age. As a result, now days there are many teachers find themselves teaching in primary school even though they have no English background or been trained for this level. Most of the English graduates are only well equipped to teach junior or senior high schools. Therefore, when they have to teach them, the challenge is how to create the quality of teaching and learning programs that match to the needs for young learners. One of the hardest things about working with young learners is that often they are preliterate. When you are working with them, you can't just write letters and words on the board and expect them to able to read what you have written. However, they can orally learn a large amount of language before they learn to read and write.